Communicating the Experience of Chronic Pain and Illness Through Blogging - Ressler, Pamela Katz; Bradshaw, Ylisabyth S; Gualtieri, Lisa; Chui, Kenneth Kwan Ho (JMIR Publications, 2012)
BackgroundAlthough more individuals are sharing their experiences with chronic pain or illness through blogging (writing an Internet web log), research on the psychosocial effects and motivating factors for initiating and maintaining a blog is lacking. ObjectiveThe objective was to examine via online questionnaire the perceived psychosocial and health benefits of blogging among patients who use this media to communicate their experience of chronic pain or illness. MethodsA 34-item online questionnaire was created, tested, and promoted through online health/disease forums. The survey employed convenience sampling and was open from May 5 to July 2, 2011. Respondents provided information regarding demographics, health condition, initiation and upkeep of blogs, and dynamics of online communication. Qualitative data regarding respondents' blogging experiences, expectations for blogging, and the perceived effects from blogging on the blogger's health, interpersonal relationships, and quality of life were collected in the form of written narrative. ResultsOut of 372 respondents who started the survey, 230 completed the entire questionnaire. Demographic data showed survey respondents to be predominantly female (81.8%) and highly educated (97.2% > high school education and 39.6% with graduate school or professional degrees). A wide spectrum of chronic pain and illness diagnoses and comorbidities were represented. Respondents reported that initiating and maintaining an illness blog resulted in increased connection with others, decreased isolation, and provided an opportunity to tell their illness story. Blogging promoted accountability (to self and others) and created opportunities for making meaning and gaining insights from the experience of illness, which nurtured a sense of purpose and furthered their understanding of their illness. ConclusionsResults suggest that blogging about chronic pain and illness may decrease a sense of isolation through the establishment of online connections with others and increases a sense of purpose to help others in similar situations. Further study involving a larger sample size, a wider range of education levels, and respondents with different types and magnitudes of illnesses will be needed to better elucidate the mechanism of the observed associations in this understudied area.